Exploring issues of power in formal mentoring programs - Jeremy W. Bohonos; Sunny L. Munn; Tonette S. Rocco; Schane D. Coker; Myrian Herlle; Mikki L. Johnson (Adult Education Research Conference, 2021)
The purpose of this project is to explore how power manifests within mentoring relationships that purport to reduce power distances and move away from traditional hierarchical models of mentoring towards reciprocal methods of mentorship. The roundtable will be a discussion of how power presents and can be proactively addressed in mentoring relationships.
Keywords: mentoring; power; privilege; relationships